A Humanities Wanderer "Lost" in Tourism Studies: A Critical Reflection. Issue 1 (2nd January 2016) - Xiao, Honggen
ABSTRACT: Auto-ethnographically, this essay attempts to tell a story of how a humanities graduate has ended up as a tourism academic, and the consequences or felt changes associated with his journey. Drawing from lived experiences along the way, the narrator offers critical reflections on (1) a farmer's son becoming an academic; (2) positioning self against others in the community; (3) authenticity—being a tourist, being yourself, and being "at home"; and (4) cultural identity—an expatriate doing China tourism research in Hong Kong. The narrative raises many questions as it unfolds itself along the way of the narrator becoming an expatriate tourism academic. The writing also sets forth the disciplinary, institutional, and cultural contexts within which the story is developed, its meanings interpreted, and implications, if any, inferred.